Population dynamics and ecology of Arcobacter in sewage - Fisher, Jenny C.; Levican, Arturo; Figueras, María J.; McLellan, Sandra L. (Frontiers in Microbiology, 2014)
Arcobacter species are highly abundant in sewage where they often comprise approximately 5-11% of the bacterial community. Oligotyping of sequences amplified from the V4V5 region of the 16S rRNA gene revealed Arcobacter populations from different cities were similar and dominated by one to three members, with extremely high microdiversity in the minor members. Overall, nine subgroups within the Arcobacter genus accounted for >80% of the total Arcobacter sequences in all samples analyzed. The distribution of oligotypes varied by both sample site and temperature, with samples from the same site generally being more similar to each other than other sites. Seven oligotypes matched with 100% identity to characterized Arcobacter species, but the remaining 19 abundant oligotypes appear to be unknown species. Sequences representing the two most abundant oligotypes matched exactly to the type strains for A. cryaerophilus group 1B (CCUG 17802) and group 1A (CCUG17801), respectively. Oligotype 1 showed generally lower relative abundance in colder samples and higher relative abundance in warmer samples; the converse was true for Oligotype 2. Ten other oligotypes had significant positive or negative correlations between temperature and proportion in samples as well. The oligotype that corresponded to A. butzleri, the Arcobacter species most commonly isolated by culturing in sewage studies, was only the eleventh most abundant oligotype. This work suggests that Arcobacter populations occupy unique niches in sewer infrastructure and are modulated by temperature. Furthermore, current culturing methods used for identification of Arcobacter fail to identify some abundant members of the community and may underestimate the presence of species with affinities for growth at lower temperatures. Understanding the ecological factors that affect the survival and growth of Arcobacter spp. in sewer infrastructure may better inform the risks associated with these emerging pathogens.